Validation methods for evaluation of ceiba honey’s growth inhibitory activity against Bacillus subtilis ATCC 6633 - Nuzul Wahyuning Diyah; Laili Irfanah; Isnaeni Isnaeni (Pharmaciana, 2020)
Agar diffusion and turbidimetry were commonly used to evaluation of   antibacterial activity of honey. However, there is no report about which one of these two methods is better. This study attempts to validate the agar diffusion method and turbidimetry used for growth inhibitory assay of ceiba honey against Bacillus subtilis ATCC 6633 based on validation parameters including Limit of Detection (LOD), linearity, precision, and selectivity. The samples were ceiba honey aqueous solutions in concentration 20%-100%. It was found that the minimum inhibitory concentration (MIC) of agar diffusion and turbidimetric methods were 35% and 30% respectively, considered as LOD. In agar diffusion method, plot of inhibitory zone diameter against log of honey concentration yields linear regression equation with r = 0.9804 and Vx0=1.06%, while r and Vx0of linear plot from % transmittance against log concentration in the turbidimetric method were 0.9748 and 1.24% respectively. The coefficient of variation (CV) in agar diffusion method were 1.78% for repeatability and 3.13% for intermediate precision) whereas CV in turbidimetric were 3.64% and 4.05% respectively. Agar diffusion and turbidimetric methods were selective because different source of ceiba honey could give different response in term of MIC. It can be concluded that the agar diffusion and turbidimetric method were valid and suitable for growth inhibitory assay of ceiba honey against Bacillus subtilis ATCC 6633 and there was no significant differences between these methods. The turbidimetry was more sensitive than the agar diffusion method because of its lower LOD and it has more simple experimental technique.